1994
DOI: 10.1111/j.1600-0447.1994.tb01533.x
|View full text |Cite
|
Sign up to set email alerts
|

A 12‐week double‐blind multi‐centre study of paroxetine and imipramine in hospitalized depressed patients

Abstract: Fifty-seven inpatients with major depression (DSM-III-R) entered a 12-week study comparing paroxetine and imipramine. Trends (not reaching statistical significance) in favour of paroxetine were seen on the Hamilton Depression Rating Scale (HDRS) and the Montgomery-Asberg Depression Rating Scale (MADRS). The UKU Side Effect Rating Scale showed a significant difference in favour of paroxetine on reduced salivation. Global evaluation of side effect symptoms showed that significantly more paroxetine patients had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…In addition, imipramine and paroxetine possess anticholinergic properties that may be responsible for memory impairments. Among selective SSRIs, paroxetine shows a relatively high affinity for muscarinic receptors and is not devoid of anticholinergic side effects (Fujishiro et al 2002), but paroxetine anticholinergic side effects are reduced in comparison to those induced by imipramine (Feighner et al 1993;Arminen et al 1994). The extended harmful effect that we observed in those tasks after chronic treatment with imipramine, but not with paroxetine, could be partially attributable to this discrepancy.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In addition, imipramine and paroxetine possess anticholinergic properties that may be responsible for memory impairments. Among selective SSRIs, paroxetine shows a relatively high affinity for muscarinic receptors and is not devoid of anticholinergic side effects (Fujishiro et al 2002), but paroxetine anticholinergic side effects are reduced in comparison to those induced by imipramine (Feighner et al 1993;Arminen et al 1994). The extended harmful effect that we observed in those tasks after chronic treatment with imipramine, but not with paroxetine, could be partially attributable to this discrepancy.…”
Section: Discussioncontrasting
confidence: 50%
“…Paroxetine induces side effects like anticholinergic and cardiovascular adverse effects but less than those of TCAs (Feighner et al 1993;Arminen et al 1994). The aim of our study was to compare in rats the effects of acute and chronic treatments with paroxetine and imipramine, a reference TCA with non-selective 5-HT and NE inhibitor properties, on learning and memory performances that require the contribution of PFC networks.…”
Section: Introductionmentioning
confidence: 99%
“…Other (less widely quoted) studies have demonstrated similar, if not greater, efficacy for SSRIs compared with TCAs in patients with severe (HAM-D score > 25 at baseline) depression (Ottevanger, 1991;Link and Dunbar, 1992;Feighner et al, 1993). For patients hospitalized with depression, equivalent efficacies have been reported between SRRIs and TCAs (Tipol et al, 1992;Arminen et al, 1994). Indeed, a recent review concludes that most of the studies that compare the antidepressant efficacy of SSRIs with TCAs, and include depressed inpatients, show no difference in efficacy between these two groups of drugs (Nierenberg, 1994).…”
Section: Efficacymentioning
confidence: 93%
“…In two of these studies, paroxetine was shown to be as effective as the comparative TCA. In the first study, paroxetine (20 to 40 mg/day) was compared with imipramine (100 to 200 mg/day) in a 12-week assessment of 57 hospitalized patients (Arminen et al, 1994). Symptom improvement from baseline was rated by the HAM-D, the MADRS, and the BDI.…”
Section: Ssris Vs Tcasmentioning
confidence: 99%